Functional meaning of rewards and interpersonal deviance in the workplace: The moderating role of basic psychological needs satisfaction - Konstantinos Papachristopoulos; Despoina Xanthopoulou (International Journal of Business Science & Applied Management (IJBSAM), 2019)
In this paper, we used self-determination theory to argue that the satisfaction of the basic psychological needs for autonomy, competence, and relatedness may act as a boundary condition that determines when and how functional meaning of rewards (i.e., when individuals perceive work-related rewards as informational or controlling) relates to interpersonal deviant behavior in the workplace. We hypothesized that informational meaning of rewards will relate negatively and controlling meaning of rewards will relate positively to interpersonal deviant behavior. Also, we expected that the former relationship will be stronger when needs satisfaction is higher (vs. lower), and the latter relationship will be weaker when needs satisfaction is higher (vs. lower). Hypotheses were tested by means of a cross-sectional study with a heterogeneous sample of 265 Greek employees. Results of hierarchical regression analyses showed that both controlling and informational meaning of rewards related positively to deviant behavior. Also, relatedness need satisfaction moderated the relationships between informational and controlling meaning of rewards with deviant behavior in a way that both facets of rewards related positively to deviant behavior in conditions of lower relatedness need satisfaction, while they were unrelated to deviant behavior in conditions of higher relatedness need satisfaction. These results suggest that the role of the functional meaning of rewards for interpersonal deviance depends on whether employees' need of relatedness is satisfied or not in the workplace.
Keywords: 650; functional meaning of rewards; interpersonal deviant behavior; psychological needs satisfaction; self-determination theory